Feeding Difficulties and Feeding Behaviors of Thai Children with Cow’s Milk Protein Allergy - Kununya Charoensriwattanakul; Kamolmart Wannaphahoon; Sirinuch Chomtho; Pantipa Chatchatee; Narissara Suratannon; Pannipa Kittipongpattana; Orapa Suteerojntrakool (International Journal of Pediatrics)
Background. Cow’s milk protein allergy (CMPA) is a common food allergy in infants and young children and may be a risk factor for feeding difficulties. Studies exploring feeding difficulties and feeding behaviors in Thai children with CMPA are scarce. Objectives. To determine the prevalence of feeding difficulties and feeding behaviors in Thai children with CMPA compared to healthy controls. Methods. A cross-sectional study was performed comparing children aged 1-6 years old diagnosed with CMPA and had eliminated cow’s milk for at least 4 months with age-matched healthy children. Feeding difficulties were evaluated using the Montreal Children’s Hospital Feeding Scale questionnaire, and feeding behaviors were measured using the Child Eating Behavior Questionnaire (CEBQ). Results. One hundred and twenty-two participants were recruited (30 children with CMPA and 92 controls). The median age of the CMPA and control groups was 31.0 (14.0, 43.3) and 40.0 (28.0, 53.8) months, respectively (p value = 0.01). The CMPA group had lower calcium, phosphorus, and zinc intake than the healthy controls. The prevalence of feeding difficulties between the two groups did not show a significant difference (36.7 vs. 43.5%, p value = 0.70). The slowness in the eating subscale of feeding behaviors exhibited a lower score in the CMPA group than in the healthy group. Feeding difficulties was positively correlated with the desire to drink (β 3.079, p value = 0.011) but negatively correlated with the enjoyment of food subscale of CEBQ among the CMPA children (β -10.684, p value < 0.001). Conclusion. Despite a similar prevalence of feeding difficulties between CMPA and healthy children, the CMPA group demonstrated some differences in feeding behaviors. The lower score of enjoyment of food and a higher score of desire to drink correlated with a higher degree of feeding difficulties in the CMPA children. The provision of appropriate nutrition for this group of children should be prioritized.